Pengaruh Pendidikan Agama Islam terhadap Akhlak Siswa di SDN Bareng Jombang - Shofwatal Qolbiyyah; Adibah Adibah (Sumbula: Jurnal Studi Keagamaan, Sosial dan Budaya, 2022)
The purpose of this study was to determine the effect of Islamic religious education on student morals at SDN Bareng Jombang. Islamic Religious Education is a learning system that covers all aspects of life needed by mankind in order to improve the appreciation and practice of Islam in social, religious, national and state life. The method used in this research is descriptive quantitative. The population in this study were students at SDN Bareng Jombang in 2018/2019 with samples in grades IV and V B. The data collection technique used observation, interviews, questionnaires and documentation. While the data analysis technique uses the Ma and Mb formulas and the T test. The conclusion from this study is that Islamic Religious Education at SDN Bareng Jombang is already good and needs to be improved so that student morals are getting better. There is no difference in the influence of Islamic religious education on the morals of SDN Bareng Jombang students, both for students who get the lowest score and those who get the highest score.